First South American Record of Winteroxylon, Eocene of Laguna del Hunco (Chubut, Patagonia, Argentina): New Link to Australasia and Malesia - Brea, Mariana; Iglesias, Ari; Wilf, Peter; Moya, Eliana Vanesa; Gandolfo, Maria Alejandra (International Journal of Plant Sciences)
Premise of research. Winteraceae, a family within the Canellales, is composed of tropical trees and shrubs broadly distributed in the Southern Hemisphere. The family is found today in eastern Australia, New Zealand, Malesia, Oceania, Madagascar, and the Neotropics across a range of dry to wet tropical to temperate climate regions. The fossil record of woods related to the Winteraceae in the Southern Hemisphere is limited to the Late Cretaceous of the Antarctic Peninsula. Here, we present a detailed anatomical description of the secondary xylem of a well-preserved trunk from the early Eocene Laguna del Hunco site, Huitrera Formation, Patagonia (Chubut Province, Argentina), that is referable to a new species of the genus Winteroxylon (Gottwald) Poole and Francis. Methodology. The wood is preserved as a siliceous permineralization; it was sectioned using standard petrographic techniques and observed under both light and scanning electron microscopy. The anatomy was compared with that of extant and fossil species of Winteraceae. Pivotal results. The diagnostic anatomical features of Winteraceae preserved in the fossil include an absence of growth rings, a lack of vessels, tracheids that are rectangular in cross section with circular bordered pits, diffuse axial parenchyma, rays showing two distinct size ranges (uniseriate-biseriate or multiseriate, 3–15 cells wide), and the presence of heterocellular rays containing sclerotic nests, cells with dark contents, and oil cells. The new fossil species most resembles extant genera within the Zygogynum s.l. clade from Australasian and Malesian rain forests; its anatomy is very similar to that of the extant genus Bubbia. The new Patagonian Winteraceae fossil wood is characterized by the presence of sclerotic nests and oil cells in the rays, which differ from those of previously described species of Winteroxylon. Conclusions. On the basis of the distinctive characters preserved, we erect Winteroxylon oleiferum sp. nov. The new fossil is the first reliable macrofossil record ...